INTEGRATING ARTIFICIAL INTELLIGENCE INTO COLLABORATIVE LEARNING TO FOSTER 21ST-CENTURY SOFT SKILLS: EVIDENCE FROM A BEST PRACTICE STUDY IN MAN 1 BANDA ACEH - Muhammad Putra Aprullah; Muhammad Sayuthi; Salsabilla Julnadi; William Ben Gunawan; Indrayani Indrayani; Raida Fuadi; Zahara Zahara; Agus Adria (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This best practice study aims to develop 21st-century soft skills in students at MAN 1 Banda Aceh through the implementation of an artificial intelligence-based collaborative learning model called KOTAK (Artificial Intelligence-Based Brain Collaboration). The study used a qualitative case study design with 39 students. Data collection was conducted through learning observations, interviews, and analysis of student activities and learning outcomes in the Integrated Economic Exploration material. The KOTAK model was designed by integrating various easily accessible AI tools, such as Google Lens, ChatGPT, and QuestionWell, to support interactive, collaborative, and problem-solving-based learning. The results showed that implementing the KOTAK model significantly improved students' critical thinking, communication, collaboration, and creativity (4C) skills. Analysis of learning outcomes indicated a 94.87% absorption rate and achievement of the curriculum objectives for the taught material. The use of the AI platform has proven to be an effective interactive medium for encouraging active student engagement, strengthening higher-order thinking, and fostering collaboration in problem-solving. This research makes an original contribution by offering and testing a contextual learning model that integrates collaborative pedagogy and AI technology in a madrasah environment, while also presenting a practical framework for developing 21st-century skills in integrated subjects such as Economics, in line with the implementation of the Merdeka Curriculum.